Chitinophaga solisilvae sp. nov., isolated from forest soil. Issue 8 (23rd August 2020) - Ping, Weiwei; Zhang, Ying; Pang, Huancheng; Zhang, Jun; Li, Dai; Li, Yuyi; Zhang, Jianli
Abstract : A Gram-stain-negative, strictly aerobic, non-motile and rod-shaped bacterial strain, O9 T, was isolated from a forest soil sample collected at Dai, Xishuangbanna, Yunnan Province, PR China. Strain O9 T grew optimally at pH 7.0, at 28‒30 °C and in the absence of NaCl. 16S rRNA gene sequence analysis placed strain O9 T within the genus Chitinophaga of the family Chitinophagaceae, with Chitinophaga terrae KP01 T (97.8 %), Chitinophaga jiangningensis JN53 T (97.7 %), Chitinophaga niastensis JS16-4 T (97.4 %), Chitinophaga qingshengii JN246 T (97.3 %) and Chitinophaga dinghuensis DHOC24 T (97.3 %) as its closest relatives. Strain O9 T hydrolysed casein, gelatin and Tween 80. It could not assimilate l -arabinose, l -rhamnose, sucrose, melibiose, gentiobiose or d -fructose as a carbon source. It was negative for esterase lipase (C8) and β -glucosidase. Phosphatidylethanolamine was the predominant polar lipid. The major respiratory quinone of strain O9 T was MK-7. Its major fatty acids were iso-C15:0 (34.2 %), C16:1 ω 5 c (20.9 %) and iso-C17:0 3-OH (12.6 %). The genomic DNA G+C content of strain O9 T was 49.0 mol% based on total genome calculations. The average nucleotide identity score between the genomic sequence of strain O9 T and that of Chitinophaga terrae KP01 T was 72.9%. The Genome-to-Genome Distance Calculator showed that DNA‒DNA hybridization values for strain O9 T and Chitinophaga terrae KP01 T were 13.6, 21.1 and 14.4%, respectively. Based on the polyphasic taxonomic data, strain O9 T represents a novel species of the genus Chitinophaga, for which the name Chitinophaga solisilvae sp. nov. is proposed. The type strain is O9 T (=CGMCC 1.12462 T =KCTC 32404 T ).